2009
DOI: 10.1038/mi.2009.2
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 in mucosal DC mediates induction of regulatory T cells in the intestine through suppression of IL-4

Abstract: Oral intake of protein leads to tolerance through the induction of regulatory T cells (Tr cells) in mesenteric lymph nodes (MLNs). Here we show that the inhibition of cyclooxygenase-2 (COX-2) in vivo suppressed oral tolerance and was associated with enhanced differentiation of interleukin (IL)-4-producing T cells and reduced Foxp3(+) Tr-cell differentiation in MLN. As a result, the functional suppressive capacity of these differentiated mucosal T cells was lost. IL-4 was causally related to loss of tolerance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 53 publications
1
33
1
7
Order By: Relevance
“…12,46 anti-inflammatory cytokines and mediators, such as interleukin (iL) -4, -5, -10, -13 and transforming-growth-factor-β (tGFβ), are released and these molecules help maintain the healthy balance of the intestinal mucosa. 47 tolerogenic dcs also inhibit pro-inflammatory responses mediated by th1 and th17 cells. 48 toll-like receptor (tLr and green lightning) signaling pathways induce upregulation of antimicrobial peptides and chemoattractants, promote iec survival (by activation of anti-apoptotic genes) and help maintain the mucosal barrier.…”
Section: The Remarkable Adaptation Of the Colonic Mucosa To Toll-likementioning
confidence: 99%
“…12,46 anti-inflammatory cytokines and mediators, such as interleukin (iL) -4, -5, -10, -13 and transforming-growth-factor-β (tGFβ), are released and these molecules help maintain the healthy balance of the intestinal mucosa. 47 tolerogenic dcs also inhibit pro-inflammatory responses mediated by th1 and th17 cells. 48 toll-like receptor (tLr and green lightning) signaling pathways induce upregulation of antimicrobial peptides and chemoattractants, promote iec survival (by activation of anti-apoptotic genes) and help maintain the mucosal barrier.…”
Section: The Remarkable Adaptation Of the Colonic Mucosa To Toll-likementioning
confidence: 99%
“…Additionally, the conversion of naive T cells into Foxp3 + Tregs is directly mediated by regulatory dendritic cells (DCs) that express increased levels of cyclooxygenase (COX)-2, IL-10, TGF-b, or IDO (28,29).…”
Section: Converts Naive T Cells Into Foxp3mentioning
confidence: 99%
“…SA as well as aspirin prevents prostaglandin formation by inhibiting cyclooxygenases (COX). Recently it was shown that the COX-2 in mucosal dendritic cells may be involved in induction of oral tolerance to dietary antigen via mediating activation of regulatory T cells (Broere et al, 2009). It may suggest an effect of SA different from that of oil emulsion in the sensitization process.…”
Section: Discussionmentioning
confidence: 99%